Report on the Nationally Determined Contribution (NDC) Analysis and SB62 Submission Stakeholder Meeting - Ng’ang’a, K. (International Livestock Research Institute, 2025)
The NDC Situational Analysis and SB62 Submission Meeting was convened to (1) solicit feedback from stakeholders on a situational analysis of Kenya’s Nationally Determined Contribution (NDC) in the agriculture sector, and (2) collect inputs into Kenya’s submission to the UNFCCC on the first workshop under Sharm el Sheikh joint work on agriculture that will be held at the 62nd meeting of the Subsidiary Bodies (SB62). The meeting brought together experts, policymakers, and stakeholders from various institutions to discuss key aspects of the NDC process, challenges, and opportunities for improvement.